2019
DOI: 10.14740/gr1133
|View full text |Cite
|
Sign up to set email alerts
|

Joint Hypermobility Syndrome Affects Response to a Low Fermentable Oligosaccharide, Disaccharide, Monosaccharide and Polyol Diet in Irritable Bowel Syndrome Patients: A Retrospective Study

Abstract: Background The low fermentable oligosaccharide, disaccharide, monosaccharide and polyol (FODMAP) diet causes significant clinical improvement in patients with irritable bowel syndrome (IBS). Joint hypermobility syndrome (JHS), defined as musculoskeletal symptoms in a hypermobile individual in the absence of systemic rheumatological disease, may be associated with functional gastrointestinal symptoms, including IBS. The aim of this study is to examine whether JHS can affect the response to the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…Evidence for management specifically in HSD/hEDS lacking–attention to: Integrated care and behavioral therapies 85 Dietary management: FODMAP diet efficacious in HSD/hEDS‐related DGBI 89 Pelvic floor dysfunction: consider early referral for anorectal physiological assessment and biofeedback/pelvic floor physiotherapy Psychology input to address psychological comorbidity …”
Section: Management Considerationsmentioning
confidence: 99%
“…Evidence for management specifically in HSD/hEDS lacking–attention to: Integrated care and behavioral therapies 85 Dietary management: FODMAP diet efficacious in HSD/hEDS‐related DGBI 89 Pelvic floor dysfunction: consider early referral for anorectal physiological assessment and biofeedback/pelvic floor physiotherapy Psychology input to address psychological comorbidity …”
Section: Management Considerationsmentioning
confidence: 99%
“…A recent publication demonstrated that hEDS patients with IBS respond better to the FODMAP diet than IBS patients without hEDS (Fragkos et al, 2019). This finding suggests that the overlap IBS/hEDS group form a distinct group with more dietary influences and that this group may be handling food and nutrients differently than those with IBS alone.…”
Section: Dietary Changesmentioning
confidence: 99%
“…The high safety profile allows for use as sole therapy in patients with symptoms not meeting the need for daily therapeutics like tricyclic antidepressants or selective serotonin reuptake inhibitors, as well as an adjunct therapeutic for patients with higher acuity disease. This finding has tremendous implications for patients with a myriad of conditions, ranging from IBD and non-responsive celiac disease to IBS and other diseases of gut-brain interaction (functional dyspepsia, etc), and is of particular note for patients with IBS/DGBI and benign hypermobility given the high efficacy of a low-FODMAP diet in this population 32 .…”
Section: Discussionmentioning
confidence: 88%